2019
DOI: 10.15199/48.2019.01.33
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic Fields and Neurodegenerative Diseases

Abstract: The aim of this work is to present the current knowledge about the possible participation of electromagnetic fields in the occurrence and also in treatment of neurodegenerative diseases. The literature data indicate both the negative and positive effects of electromagnetic fields and not allow to draw unambiguous conclusions. Undoubtedly, the topic is still open and needs further intensive research to finally assess the mechanism of action of the electromagnetic field on neurodegenerative diseases. Streszczeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…Some of these important factors include modulating waveform (potential excitation signal, Ψ), time interval, frequency, and amplitude of the triggering waveform 17 . At this condition, every arrhythmia and deviation from the normal characteristics of this harmony can be considered as the risk factors about the neuronal diseases via the neuronal electrical regulation process 18 .…”
mentioning
confidence: 99%
“…Some of these important factors include modulating waveform (potential excitation signal, Ψ), time interval, frequency, and amplitude of the triggering waveform 17 . At this condition, every arrhythmia and deviation from the normal characteristics of this harmony can be considered as the risk factors about the neuronal diseases via the neuronal electrical regulation process 18 .…”
mentioning
confidence: 99%
“…Nevertheless, several studies have reported that EMF could affect brain function leading to mental and various types of neurological disorders (Pall, 2016;Terzi, Ozberk, Deniz, & Kaplan, 2016;Wyszkowska, Jankowska, & Gas, 2019). Moreover, in our previous studies, we have shown the deleterious effects of exposure to 900 MHz radiofrequency waves (RFW) on brain function including memory impairment and oxidative damage (Akbari, Jelodar, & Nazifi, 2014;Azimzadeh et al, 2018).…”
Section: Introductionmentioning
confidence: 94%
“…Stimulation of the deep brain has shown outstanding performance for people with neurological problems such as Parkinson’s disease, essential tremor and so on [1]. Currently, the simulation method has been deployed using permanently implanted electrodes [2] and chemicals [3], acoustic [4], electromagnetic [5], or optical [6] signals.…”
Section: Introductionmentioning
confidence: 99%